Biomechanical Evaluation of a Femoral Implant for Hip Resurfacing Arthroplasty in Dogs: An Ex Vivo Study - Perez Neto, Daniel M.G.; Muzzi, Leonardo A.L.; Santos, Fábio L.; Muzzi, Ruthnea A.L.; Kawamoto, Fernando Y.K.; Mesquita, Luciane R. [UNESP]; Minto, Bruno W. [UNESP] (Thieme, 2024)
Objective: The objective of this study was to assess the stability of the femoral component of a hip resurfacing arthroplasty prosthesis in canine cadaveric bone using a biomechanical test. Study Design: Twenty adult dog cadavers were utilized, from which both femoral bones were extracted and preserved for experimentation. For each pair of femurs from the same animal, one femur underwent implantation of the hip resurfacing arthroplasty prosthesis, while the contralateral femur remained intact. All femoral specimens underwent flexo-compression biomechanical testing, with variables including maximum load (ML), load at collapse (LC), displacement at maximum load (DML), displacement at collapse (DC), and stiffness (k) being analysed. Subsequent to the biomechanical evaluation, the femoral specimens were radiographed to assess failure behaviour. Results: The prosthesis group showed a reduction of 22% (p ≤ 0.050) for the ML variable and 27% (p ≤ 0.05) for LC values. The prosthetic group supported a mean ML equivalent to six times the body weight of the animals whose bones were tested. No significant disparities were detected between the groups for the other analysed variables (DML, DC, and k). Similar failure patterns, such as fractures in the femoral neck region, were observed in specimens from both groups. Conclusion: The hip resurfacing arthroplasty prosthesis demonstrated biomechanical performance with no differences in DML, DC, and k but showed inferior performance in ML and LC when compared with intact femurs in the ex vivo setting.
Keywords: biomechanical test; femoral prosthesis; hip arthroplasty; hip dysplasia; osteoarthritis